2009
DOI: 10.1177/105268460901900104
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Teacher Success Using Teacher Selection Practices and Classroom Performance Assessment

Abstract: This study evaluated the predictive validity of two preemployment screening devices-the Urban Teacher Perceiver Interview and the Academic Skills Assessment portion of the Praxis Series test-as used by an urban highneed and hard-to-staff school district. Specifically, we compared predictor scores with subsequent teacher assessment scores generated through the Teacher Performance Assessment process. Three research questions directed this study: Is the Urban Teacher Perceiver Interview an effective predictor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Since that time a variety of different proxy measures of teacher intelligence have been explored (McEachin & Brewer, 2011). These have included: general measures of intelligence (Morsh & Wilder, 1954), standardized test scores (D'Augostino & Powers, 2009;Gimbert & Chelsey, 2009;Schalock, 1979;Webster, 1988;Wise et al, 1987) and academic ability (Heinz, 2013;Schalock, 1979;Wise et al, 1987;). The following section discusses the literature on each of these in further detail.…”
Section: Instructor Selection Methods In Industrymentioning
confidence: 99%
“…Since that time a variety of different proxy measures of teacher intelligence have been explored (McEachin & Brewer, 2011). These have included: general measures of intelligence (Morsh & Wilder, 1954), standardized test scores (D'Augostino & Powers, 2009;Gimbert & Chelsey, 2009;Schalock, 1979;Webster, 1988;Wise et al, 1987) and academic ability (Heinz, 2013;Schalock, 1979;Wise et al, 1987;). The following section discusses the literature on each of these in further detail.…”
Section: Instructor Selection Methods In Industrymentioning
confidence: 99%
“…. necessary for safe and effective practice" (Educational Testing Service, 2019, p. 5), but Gimbert and Chesley (2009) found "no statistically significant relationship" between the Praxis core assessment and subsequent teacher performance (p. 49).…”
Section: Access To Gifted Educationmentioning
confidence: 99%
“…A total of 12 studies reported the use of basic skills test scores. Blue et al (2002), Gimbert and Chesley (2009), Goldhaber, Liddle, and Theobald, (2013), Henry et al (2013), and Smith, Wageman, Anderson, Duield, and Nyachwaya (2019) used Praxis 1 composite scores. In all of their three studies, Buddin and Zamarro (2009a,b,c) focused on California Basic Educational Skills Test (CBEST) composite scores.…”
Section: Measures Used To Assess Teachers' Cognitive Abilitiesmentioning
confidence: 99%
“…Unfortunately, a few studies had small sample sizes, raising concerns about low statistical power. Moreover, taking a closer look at the studies that reported information on the initially considered pool of participants reveals that in some studies the sample sizes were drastically reduced, e.g., due to the unavailability of administrative data for large numbers of teachers (e.g., Gimbert & Chesley, 2009). It has long been known that sample size reduction can attenuate the generalizability of indings and represents a potential threat to their validity if the teachers who could not be reached, dropped out, or were excluded difer systematically from those who remained in the sample (e.g., Miller & Hollist, 2007).…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation